The Mediating Role of Self-Esteem in the Relationship Between Psychological Capital, Academic Engagement, and Academic Procrastination with Psychological Well-Being Among Al-Diwaniyah Students in Iraq - Almurumudhe, Layth Khalid Abdlhussein; Mehdad, Ali; Johni, Ahmed Abdulkadhim; Yousefi , Zahra (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: This study aimed to investigate the mediating role of self-esteem in the relationship between psychological capital, academic engagement, and academic procrastination with the psychological well-being of high school students in Al-Diwaniyah, Iraq.Methods and Materials: This applied, descriptive-correlational study employed a structural equation modeling design. The statistical population included all high school students in Al-Diwaniyah, Iraq, during the first semester of the 2023-2024 academic year. A total of 250 students were selected using a multi-stage cluster random sampling method, and finally, 194 students completed the questionnaires. The questionnaires used in this study included Ryff's Psychological Well-Being Scale (1989), Solomon and Rothblum's Academic Procrastination Scale (1984), Fredericks et al.'s Academic Engagement Scale (2004), Nguyen et al.'s Psychological Capital Questionnaire (2012), and Rosenberg's Self-Esteem Scale (1965). Data were analyzed using SPSS version 26 and AMOS version 24.Findings: The results indicated a significant positive relationship between psychological capital and academic engagement with self-esteem and psychological well-being (p < .01) and a significant negative relationship between academic procrastination with self-esteem and psychological well-being (p < .01). Additionally, there was a significant positive relationship between self-esteem and psychological well-being (p < .01). Furthermore, self-esteem partially mediated the relationship between psychological capital, academic engagement, and academic procrastination with psychological well-being.Conclusion: Based on the findings of the present study, it can be concluded that fostering self-esteem through the development of psychological capital, increasing academic engagement, and reducing procrastination can improve the psychological well-being of high school students in Al-Diwaniyah, Iraq.